Estimating income variances by probability sampling: A case study - Muhammad Akbar Ali Shah; M. Aleem (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2010)
The main focus of the study is to estimate variability in income distribution of households by conducting a survey. The variances in income distribution have been calculated by probability sampling techniques. The variances are compared and relative gains are also obtained. It is concluded that the income distribution has been better as compared to first Household Income and Expenditure Survey (HIES) conducted in Pakistan 1993-94.
Keywords: 330; Variability; Income distribution; Probability Sampling; Relative gain; Gini Coefficient